Application of functional training in high sports and recreation - Mikic, B.; Bajric, O.; Stankovic, N.; Ivanek, V.; Petrovic, Z. (Sports Science and Health, 2016)
The aim of this work is to determine attitudes if trainers about possibilities and efficiency of application of functional training in high sports and recreation. In order to obtain relevant information about the importance of functional training in top sport and recreation, the survey was conducted on a sample consisting of 25 coaches of different age groups, gender, branch of sport and sports experience. The survey results showed that functional training is one of the most popular systems of training in top sport and recreation and that coaches use in their practical work. According to the respondents coach for functional training is important to point out that it is based on exercises that include our whole body and thereby leads to the activation of more muscle groups at the time of its execution. It affects the development of motor skills such as strength, power, coordination, balance, flexibility, speed, muscular endurance. Trainers also claim that functional training effects the development of energy systems (phosphate, glycolytic and aerobic), and reduction of body fat (subcutaneous and visceral), toning and increasing muscle mass, subjective sense of power and regulating stress levels.